Hang in There : Stock Market Reactions to Withdrawals of COVID-19 Stimulus Measures - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2020)
The COVID-19 pandemic prompted unprecedented economic stimulus worldwide. We empirically examine the impact of a withdrawal of fiscal stimulus policies on the stock markets. After constructing a database of withdrawal events, we use event study analysis and cross-country regressions to assess the difference between the pre- and post-event stock price returns. We find that markets react negatively to premature withdrawals-defined as withdrawals at a time when the daily COVID cases are high relative to their historical average-likely reflecting concerns about the withdrawal impact on the prospects for economic recovery. The design of a successful exit strategy from COVID-19 policy responses should account for these concerns.